Finite element simulation of drying of longan fruit - S. Janjai (2018)
A two-dimensional finite element model has been developed to simulate moisture diffusion in longan fruit during drying and moisture diffusivities of the components of longan fruit determined experimentally are used in this simulation. Shrinkage of the flesh of longan during drying is also taken into account. The finite element model is programmed in Compaq Visual FORTRAN version 6.5. This finite element model satisfactorily predicts the moisture diffusion during drying. Moisture contents in the different components in the longan fruit during drying are simulated. Moisture content profiles of the longan fruit are also predicted. Knowledge gained from this study will be useful in the understanding of the transport processes in the different components of the longan fruit.